The Ex Ante Incentive Compatible Core in the Absence of Wealth Effects - Forges, Francoise; Mertens, Jean-Francois; Vohra, Rajiv (Econometrica, 2002)
In a differential information economy with quasi–linear utilities, monetary transfers facilitate the fulfillment of incentive compatibility constraints: the associated ex ante core is generically nonempty. However, we exhibit a well–behaved exchange economy in which this core is empty, even if goods are allocated through random mechanisms.